Lichen planus occuring after Coronavirus disease-2019: A case report - Zuhal Metin; Koray Durmaz; Deniz Unluer Kapiskay (Galenos Publishing House, 2022)
The novel Coronavirus disease-2019 (COVID-19), which emerged in December 2019 and caused an unexplained viral pneumonia, rapidly spread worldwide within a few months. A pandemic was declared by the World Health Organization in March 2020. Several cutaneous manifestations of the disease among patients with COVID-19 have been reported. Thus far, the most frequently reported cutaneous findings are morbiliform rash, urticarial lesions, purpuric lesions, oral vesicles, and pityriasis rosea. This report presents a case of lichen planus secondary to COVID-19 and its histopathological findings, which is rarely reported in the literature.